2009
DOI: 10.1089/jwh.2008.1211
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cervical Cancer Screening Guidelines in Patient Education Materials

Abstract: Background: Adjunct human papillomavirus (HPV) testing with cervical cytology (Pap test) is one option that can increase screening intervals for women aged Ն30 years who have concurrent negative (normal) test results. Previous research suggests that most women are unaware of the relationship between HPV and cervical cancer. In addition, patients often do not understand the significance of their HPV test results, let alone the implications of negative results for future cervical cancer risk or screening options… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Evaluations of printed HPV (n=21) and cervical cancer prevention (n=69) educational materials designed to enhance patient knowledge and awareness found that most materials had readability levels higher than 8th grade and low suitability. 2628 Brandt et al 26 also identified poor HPV content for the majority of HPV educational materials; however, the brochure utilized in the present analysis was not included in the evaluation. HPV educational materials may be especially problematic for Latinas.…”
Section: Discussionmentioning
confidence: 81%
“…Evaluations of printed HPV (n=21) and cervical cancer prevention (n=69) educational materials designed to enhance patient knowledge and awareness found that most materials had readability levels higher than 8th grade and low suitability. 2628 Brandt et al 26 also identified poor HPV content for the majority of HPV educational materials; however, the brochure utilized in the present analysis was not included in the evaluation. HPV educational materials may be especially problematic for Latinas.…”
Section: Discussionmentioning
confidence: 81%
“…14 The 22-page educational brochure was written at a sixth grade reading level. 15 These materials were distributed to patients in the intervention group after they completed the baseline survey.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the discussion and research regarding patient education materials has been limited to relationships between low literacy and patient decision making, medication administration, communication, and self-care management of chronic diseases. Numerous studies have been conducted on the development and evaluation of easy-to-read patient education materials (Roland et al, 2009;Rudd, 2010;Wilson, Brown, & Stephens-Ferris, 2006), yet gaps exist in the literature on easy-to-read materials focused on temporary treatments such as self-care management of radiation side effects. The current study sought to address that disparity.…”
Section: Literature Review Why Patients Need Information They Can Commentioning
confidence: 99%